Design and development of an online platform for skill exchange - Chen, Huanhuan (2019)
Nowadays, people are constantly required to exchange skills and services with others as our society becomes increasingly specialized. Owing to advances in Information Communication Technologies (ICT), the longstanding practice of bartering has now taken the form of sophisticated online exchange platforms, where individuals can easily match someone online to swap skills or services. These platforms have managed to overcome the original obstacles of bartering, such as physical distance limitations and matching difficulties, with modern technologies including remote communication and big data. As these skill exchange platforms grow in popularity, some common issues have surfaced. The project aims to design and develop a new generation of online skill exchange platform “MESK.IO” (MySkill), which innovatively integrates cryptocurrencies to improve critical aspects of a typical skill exchange platform, including transaction security, data reliability, privacy protection, and user activity. This project covers the complete software development lifecycle from requirement analysis to prototyping to implementation and finally to deployment and testing. It includes the development of a cross-platform client application, a database server and a series of smart contracts for a custom cryptocurrency token.